1993
DOI: 10.1212/wnl.43.12.2519
|View full text |Cite
|
Sign up to set email alerts
|

Lateralizing signs in intractable partial epilepsy

Abstract: We evaluated the accuracy and interobserver variability of selected ictal and postictal behavioral changes. Three observers, blinded to clinical history, EEG, and side of surgical resection, analyzed videotapes of 166 seizures in 38 patients, looking for lateralizing signs. Twenty-seven patients with temporal lobe resections were seizure-free for > or = 1 year postoperatively, and 11 with extratemporal resections had at least 90% reduction in seizures > or = 1 year postsurgery. The epileptogenic region (ER) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
138
2
5

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(153 citation statements)
references
References 0 publications
8
138
2
5
Order By: Relevance
“…The predominance of unilateral upper limb automatisms in group 1 seizures was also found by Saygi et al 16 , who also reported, as in our study, a larger incidence of leg automatisms after the first five seconds of ictal onset in group 2 patients. UDP occurred in 16% of the seizures, a less expressive result to that observed in other studies 6,8,9,26 . This feature was always contralateral to the EA matching with other reports 6,8,28,29 and confirming its lateralizatory value.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…The predominance of unilateral upper limb automatisms in group 1 seizures was also found by Saygi et al 16 , who also reported, as in our study, a larger incidence of leg automatisms after the first five seconds of ictal onset in group 2 patients. UDP occurred in 16% of the seizures, a less expressive result to that observed in other studies 6,8,9,26 . This feature was always contralateral to the EA matching with other reports 6,8,28,29 and confirming its lateralizatory value.…”
Section: Discussioncontrasting
confidence: 70%
“…Ictal speech occurred mainly during right temporal seizures as reported by others 18,34 suggesting nondominant temporal EA 18,26,35,36 . It seems to result of functional nondominant temporal lobe impairment by epileptic discharges and consequent hyperfunction of the dominant hemisphere for language 35 .…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…A subsequent study showed that although dystonic posturing had good positive predictive value for the side of seizure onset there was not good agreement between different observers as to its presence or absence in individual patients (4). Such a lack of agreement limits the clinical utility of a lateralizing sign.…”
mentioning
confidence: 99%